EFEKTIVITAS ARANG AKTIF BONGGOL JAGUNG DENGAN VARIASI MASSA DAN WAKTU KONTAK DALAM MENGURANGI KADAR TIMBAL (Pb) PADA LARUTAN PESTISIDA MENGANDUNG TIMBAL - Khoirunnisa Dyah Kartikasari; Nur Endah Wahyuningsih; Nurjazuli Nurjazuli (Jurnal Kesehatan Masyarakat (Undip), 2018)
Efforts to increase agricultural production with the aim that agricultural crops are not damaged by pests and diseases, one of them by using pesticides.. Approximately 99.9% of pesticides used enter and pollute the environment. Preliminary test results indicate that lead levels in agricultural waste exceed the specified quality standard. This research aims to determine the effectiveness of corncob activated charcoal with mass and contact time variation to reduce lead levels in pesticide solution. The type of research used is true experiment with the pretest-postest control-group design. The sample used is an artificial pesticide solution of Dithane M 45 80 WP which dissolved using aquadest. Analysis of the data used to test the hypothesis is by two way ANOVA test with a 95% confidence level. The results showed lead levels before treatment of 0.238 mg/l. After treatment using corn cobs activated charcoal with mass and contact time variation of lead content decreased, with the highest decrease in variations in mass of 200 gram and contact time of 50 minutes with a percentage of 76,27%. The results of the two way ANOVA analysis p-value values in both variables are 0.134 in the mass variable and 0.401 in the contact time variable where the result is> 0.05 so that there is no difference in the decrease in lead (Pb) in lead pesticide solution.The conclusion of this study is that corn cobs activated charcoal can reduce lead levels in pesticide solutions with an average of 49,90%, but have not been able to reduce lead levels to the specified quality standards.